Longitudinal association between self-rated health and psychological well-being in a sample of Spanish university graduates - Maria Vasilj; Estefanía Toledo; Prado Silván-Ferrero; Encarnación Nouvilas-Pallejá; Alessandra Jarufe; Leticia Goni; Maira Bes-Rastrollo; Miguel Ruiz-Canela (PLoS ONE, 2025)
Purpose Previous research has shown that psychological well-being (PWB) is associated with self-rated health (SRH) over time, but limited research has explored the reciprocal association. This study examined the longitudinal association between self-rated health and subsequent psychological well-being in a Spanish cohort. Methods Data were collected from participants of the “Seguimiento Universidad de Navarra” (SUN) Project, a dynamic university graduate cohort study. Psychological well-being was measured using the Ryff scale. Multivariable linear regressions analyse assessed the relationships between self-rated health, measured at study’s baseline and after 4 years, and psychological well-being measured after a mean follow-up of 14.6 years. The association with Ryff’s six dimensions (self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth) was also assessed. Results A total of 2,927 participants, mean age 38.7 years (SD = 11.2) at pre-baseline, 55.5% women, were followed-up for a mean of 14.6 years (SD 0.7). Compared to participants reporting poor/fair health, those with excellent self-rated health at baseline showed substantially higher subsequent psychological well-being scores (ajusted β = 15.1, 95% CI: 11.4–20.3) and were three times more likely to have above-median psychological well-being (adjusted OR=3.0, 95% CI: 1.8–4.8). A dose-response relationship was observed across self-rated health categories, with significant associations for all PWB dimensions. Additionally, self-rated health improvements during the first 4 years were associated with higher subsequent psychological well-being scores. Conclusions Self-rated health showed a direct, long-term association with subsequent PWB among Spanish university graduates, suggesting that perceived health status may be an important determinant of future PWB. However, our findings are limited by the single measurement of PWB and the use of self-reported measures. Further studies in more diverse populations are warranted to confirm these results.